UCAPAN TIDAK LANGSUNG DALAM BAHASA INGGRIS DAN BAHASA BATAK (SUATU ANALISIS KONTRASTIF) - Hutabarat, Meilani Celia (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This study is about Indirect Speech in English and Batak language. The research questions are what are the types of indirect speech in English and Batak language and what are the similarities and defferences Indirect Speech in both languages. The aim of the research is an attempt to identify, to describe the types and to analyze the indirect speech in English and Batak language contrastively. In collecting data, the writer asks 4 informants, who can speak Batak Language well. The genders of informant are male and female approximately 45-60 years old who stay in Manado 20-30 year. In English data, the writer took an example of Indirect Speech from the book written by Quah, Josephin (1993). The writer collected data and identified the sentences which refers to indirect speech in English and Batak language. The writer also described the types of Indirect speech in English and Batak language and contrast them to find out the similarities and the differences of Indirect Speech by using the concept of Quick, dkk (1973:341) and Lado descriptively. The result of this investigation shows that English has indirect speech as well as Batak language and also has the similarities and differences. In the similarities, English and Batak language have the same in the types and form as quotation marks, question sentences, statements, commands, exclamations and also changes in the time and place. In the differences, English has changed in to be and auxiliary verbs, while Batak language has not. Key words:Â Â Â Indirect Speech, English and Batak Language, Contrastive Analysis.